The party's over - Behm, Marc 1925-2007; Reed, Oliver 1938-1999; Lynn, Ann 1933- (British Film Institute, 2010)
"Enigmatic young Melina has fallen in with a group of Chelsea beatniks, catching the attention of the gang's defiant leader Moise (Oliver Reed). But wild and drunken partying has terrible consequences, and when Melina's fiancé Carson begins investigating, the shocking truth is soon revealed. Written by Marc Behm and scored by the legendary John Barry, this controversial film originally fell foul of the British censors, forcing director Guy Hamilton to remove his name from the credits, but is now finally made available in its never-before-seen pre-release version."
Original: UK, 1963-1965
Bildformat 1.66:1
Special features: presented in both High Definition and Standard Definition ; Alternative theatrical release cut (Blu-ray only, 92 min) ; Alternative theatrical release sequences (DVD only, 18 min) ; "The Party" (R A Ostwald, 1962, 16 min): a time-capsule short about an art school get-together ; "Emma" (Anthony Perry, 1964, 12 min): an expressive meditation on the loss of innocence, from the producer of "The Party's Over" ; Fully illustrated booklet with contributions by Guy Hamilton, Andrew Roberts, William Fowler and Vic Pratt
Verlagsnummer BFIB1057
Keywords: Film; DVD-Video; Blu-Ray-Disc